The Effect Of Green Coconut Water On The Pain Of Dysminorea In Adolescent Women In Lubuk Pakam Pekan Village In 2023 - Pitriani .; Juni Mariati Simarmata; Lismawati .; Yohanna Adelina; Syatriawati .; Isni Hijriana (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Some married couples have difficulty in choosing a family planning method. The low interest in MKJP is influenced by individual perceptions of threats and considerations of profit and loss. Individual perceptions are influenced by factors, namely age, education, knowledge, number of children, exposure to information sources and economic conditions. The purpose of this study was to determine the factors that influence couples of childbearing age in choosing implant contraceptives. This research method is analytic using cross sectional analysis. The number of samples in this study was 20 people. The tools used in the study used a statement questionnaire and the respondent's personal data listed in the questionnaire. The results of the analysis showed that the knowledge factor had an influence on the choice of implant contraception with a p-value of 0.007 < 0.05. Educational factors have an influence on the choice of contraceptive implants with a p-value of 0.013 < 0.05. The parity factor has an influence on the choice of contraceptive implant with a p-value of 0.032 < 0.05. Most of human knowledge is obtained through the sense of sight and the sense of hearing. One of the factors that influence the use of contraception is knowledge. Limited knowledge will affect the mother's choice of contraceptive methods. Correct knowledge about family planning programs, including about various types of contraception, will enhance community participation in family planning programsIn conclusion, couples of childbearing age who choose to use implant contraceptives are generally influenced by factors of knowledge, education and parity.